2023
DOI: 10.1071/pc22037
|View full text |Cite
|
Sign up to set email alerts
|

Do small overwater structures impact marine habitats and biota?

Abstract: Small overwater structures (SOWS) such as residential docks are common along marine shorelines. Large overwater structures like ferry terminals and commercial piers cast shadows that impair submerged aquatic vegetation and habitat, and alter salmon behaviour and migration. Because of large overwater structure impacts, it is possible that SOWS may also impact marine habitats and organisms. Here, we review the evidence for marine SOWS impacts, finding that relatively little research has been dedicated to the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This highlights a tremendous decline in estuarine species abundance and richness in the section of Yaquina Bay that has been most altered by development in the last four decades (Figure 2). Similar declines in abundance have been observed following waterfront development in the southeast United States, where demersal fish and epibenthic crustaceans were less abundant in stretches of shoreline altered by rubble or bulkheads [38], while a broader synthesis aimed at evaluating the ecological impacts of overwater structures (OWSs) in the U.S. Pacific Northwest [3] found that OWSs reduce natural habitat (seagrassess) and prey (abundance and diversity of invertebrate species), and affect the movement, migration, and feeding behaviors of salmonids. Changes to Yaquina Bay have also affected community composition, as most measures of biodiversity declined between surveys.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This highlights a tremendous decline in estuarine species abundance and richness in the section of Yaquina Bay that has been most altered by development in the last four decades (Figure 2). Similar declines in abundance have been observed following waterfront development in the southeast United States, where demersal fish and epibenthic crustaceans were less abundant in stretches of shoreline altered by rubble or bulkheads [38], while a broader synthesis aimed at evaluating the ecological impacts of overwater structures (OWSs) in the U.S. Pacific Northwest [3] found that OWSs reduce natural habitat (seagrassess) and prey (abundance and diversity of invertebrate species), and affect the movement, migration, and feeding behaviors of salmonids. Changes to Yaquina Bay have also affected community composition, as most measures of biodiversity declined between surveys.…”
Section: Discussionmentioning
confidence: 73%
“…Physical development, including shoreline armoring and construction of hardened structures, disrupts benthic communities, thereby reducing prey resources for nearshore fish and wildlife [1] and habitat available for epibenthic crustaceans [2]. It is possible that even small, human-built structures influence habitat structure, fish distribution, migration, feeding behavior, and availability of prey resources [3]. Chemical alterations, in the form of nutrient and pollutant inputs, have effects ranging from altering primary productivity and microbial community composition to changing community structure [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%